Impact of socioeconomic position on the utilization of rehabilitation services among the Chinese older adults disabled by injury - Wang, Yi-Ran; Luo, Ya-Nan; Fan, Ya-Lin; Fan, Yun-Yi; Zheng, Xiao-Ying (Frontiers in Public Health, 2023)
Aim This study aimed to explore the utilization of rehabilitation services and associated socioeconomic position (SEP) factors among Chinese older adults disabled by injury. Methods Data from the second China National Sample Survey on Disability (CSSD) were used in this study. Chi-square test was used to analyze the significant differences between groups, and binary logistic regression model was used to calculate the odds ratios and 95% confidence intervals for socioeconomic factors associated with utilization of rehabilitation services among Chinese older adults disabled by injury. Results Among the older adults disabled by injury in the CSSD, the gap between demand and utilization of medical treatment, assistive devices and rehabilitation training were around 38, 75, and 64%, respectively. This study revealed two relationship patterns (“high-low-high” and “low-high-low”) among SEP, prevalence of injury-caused disability and odds of utilization of rehabilitation services among the Chinese older adults disabled by injury, that is, the older adult with higher SEP have a lower prevalence of injury-caused disability, but a higher odds of utilization of rehabilitation services; conversely, the older adults with lower SEP have a relatively higher prevalence but a lower odds of utilization of rehabilitation services. Conclusion There is a large gap between the high demand and low utilization of rehabilitation services among the Chinese older adults disabled by injury, especially for those living in the central or western regions or rural areas, without insurance or disability certificate, having the annual household per capita income lower than the national average or lower educational level. Strategies to improve the disability manage system, to strengthen the chain of “information discovery-information transmission-rehabilitation services supply-continuous health monitoring and management” for the older adults disabled by injury are warranted. In view of the poor and illiterate groups among the disabled older adults, to enhance medical aids and popularize the scientific information to compensate for the lack of affordability and awareness of rehabilitation services utilization is essential. In addition, it is necessary to further expand the coverage and improve the payment system of medical insurance for rehabilitation services.